Cumulative Risk on Oxytocin-Pathway Genes Impairs Default Mode Network Connectivity in Trauma-Exposed Youth - Zeev-Wolf, Maor; Levy, Jonathan; Ebstein, Richard P.; Feldman, Ruth (Frontiers in Endocrinology, 2020)
Abstract Background: While the default mode network (DMN) is a core neural network sustaining the sense of self, little is known about its developmental trajectory, particularly on factors associated with its coherence into a functional network. In light of research indicating that DMN functionality in adults is sensitive to stress-related conditions, we examined the contribution of genetic variability on oxytocin-pathway genes to DMN connectivity in youth exposed to chronic war-related trauma in relation to PTSD and anxiety symptoms measured across the first decade of life. Methods: Following a cohort of war-exposed children from early childhood, we imaged the brains of 74 preadolescents (age 11-13 years; 39 war-exposed) during rest using magnetoencephalography (MEG). A cumulative risk index on oxytocin-pathway genes was constructed by combining SNPs on five genes previously linked with social deficits and psychopathology; OXTR rs1042778, OXTR rs2254298, OXTRrs53576, CD38 rs3796863, and AVPR1A RS3. In early childhood, children's avoidant response to trauma reminders was observed and in late childhood children's anxiety disorders diagnosed as predictors of disruptions to DMN theta connectivity, the oscillatory band associated with the immature brain. Results: Higher genetic vulnerability on oxytocin-pathway genes predicted greater disruptions to DMN theta connectivity, suggesting that oxytocin-system functionality may buffer the effects of chronic early stress on brain maturation. Avoidant symptoms in early childhood and the existence of a generalized anxiety disorder in later childhood were related to impaired DMN connectivity. In combination, stress exposure, oxytocin-pathway genes, and stress-related symptoms explained 24.6% of the variance in DMN connectivity, highlighting the significant effect of stress on the maturing brain. Conclusions: Our findings are first to link the oxytocin system and maturation of the DMN, a core system sustaining the emerging self, in youth reared in context of stress and trauma. We found that stress-related disorders, particularly young children's avoidant symptoms carry negative effects on DMN maturation a decade later, highlighting the need to further explore children's avoidant response to chronic trauma. The link between lower genetic risk on oxytocin-pathway genes and DMN coherence underscores the potential involvement of the oxytocin system in buffering the effects of chronic early stress on brain maturation.